2019
DOI: 10.3390/pharmacy7040150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sales Promotion Techniques on Consumers’ Purchasing Decisions at Community Pharmacies

Abstract: This research aims to identify the most prevalent and impactful sales promotion tools used by pharmaceutical companies on consumers’ purchasing decisions at community pharmacies. A cross-sectional study design was carried out using the non-repeated random sampling technique. Standardized questionnaires were administered by means of face-to-face interviews or via emails. The relative importance of prevalence (RIP) and the mean evaluation of effectiveness (MEE) were determined for all studied marketing tools for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Marketing operations in wholesale organisations may also include merchandising activities, such as in-store activities and the development of effective visual displays in retail stores, to attract customers' attention and motivate them to make purchases of the product (Mills, 2007; Jain et al. , 2014; Ben Said et al. , 2019).…”
Section: Core Operations Of Wholesale Organisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marketing operations in wholesale organisations may also include merchandising activities, such as in-store activities and the development of effective visual displays in retail stores, to attract customers' attention and motivate them to make purchases of the product (Mills, 2007; Jain et al. , 2014; Ben Said et al. , 2019).…”
Section: Core Operations Of Wholesale Organisationsmentioning
confidence: 99%
“…Marketing is as a core operation that provides value-added services, such as catalogue creation, trade advertising and trade-show representation (Hung, 2012). Marketing operations in wholesale organisations may also include merchandising activities, such as in-store activities and the development of effective visual displays in retail stores, to attract customers' attention and motivate them to make purchases of the product (Mills, 2007;Jain et al, 2014;Ben Said et al, 2019). Delivery was also defined in the literature as a core operation of wholesale organisations (Hook, 2004;Lorenzi, 2014).…”
Section: Core Operations Of Wholesale Organisationsmentioning
confidence: 99%
“…[ 1 ] This technique is highly effective, as MRs communicate the merits of a particular product directly to physicians. [ 5 ] The literature has reported that even physicians themselves do not deny the effect of MRs on their prescribing habits. [ 6,7 ] The type and frequency of interactions between physicians and MRs have received increased scrutiny from many stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…The state spends the most money on drugs with a price of over 500 rubles (54%). But in packages, on the contrary, the segment belonging to the minimum price range of up to 50 rubles (51%) occupies the maximum share [35].…”
mentioning
confidence: 98%